Intranet Portal Assessment Tool - M. Mohamad Noorman;; A.J. Kamarularifin (Universiti Sains Islam Malaysia, 2024)
This study was undertaken with the purpose to unfold and understand individual intranet utilization and their corresponding determinants and impacts. The conduct of this study was using multiple-case design approach involving mixed methods i.e. qualitative and quantitative approach. Four organizations were involved in the study namely Malaysia Airport, Telekom Malaysia, Tenaga Nasional and Petroliam Nasional. Preliminary studies involving interviews, observation and review of materials (i.e. the intranet itself) were undertaken to understand the phenomenon of intranet utilization, followed by a survey with the purpose of validating the developed theoretical model and testing the formulated hypotheses. Three groups of detenninants i.e. organizational characteristics, intranet characteristics and individual characteristics were investigated against individual intranet utilization measured in terms of utilization modes. utilization for decision support and utilization for knowledge sharing. Four organizational characteristics were investigated being top management support, technical user support, functional integration and subjective norm. Four intranet characteristics were examined being task-fit, information quality, systems quality and service quality. Four individual characteristics were explored being web efficacy, personal IT innovativeness, intranet experiences and length of service. In addition, the three intranet utilization constructs i.e. utilization modes; utilization for decision support and utilization for knowledge sharing were investigated against individual performance measured in terms of task productivity, task innovation and personal sense of accomplishment. Based on the analysis of 359 responses collected using stratified random sampling, it was discovered that all the conceptualized determinants were indeed significantly related with intranet utilization. Likewise, the three conceptualized intranet utilization variables were also found to be significantly related with individual performance. Upon further analyses unveiled that except for top management support, length of sewice and intranet experiences, all other variables from the three groups of determinants were strong predictors of intranet utilization. The major contribution of the study can be assessed from three perspectives i.e. theoretical, methodological and practical. From the theoretical viewpoint, it has developed an empirical-based framework that represents the phenomenon of intranet utilization and its corresponding determinants and impacts in the context of Malaysian users. From the methodological viewpoint, it has developed instruments which can be further tested in other research settings. From the practical viewpoint, the developed instrument can be utilized to evaluate individual utilization behaviors as well as their determinants and impacts. Accordingly, a tool was developed which can be used to gauge intranet .utilization behavior and its corresponding determinants and impacts.